2012
DOI: 10.1017/s003329171200222x
|View full text |Cite
|
Sign up to set email alerts
|

Family history of alcohol dependence modulates functional neurophysiology in mood/anxiety disorders

Abstract: This study demonstrates subtle impairments during planning in FH+ compared with FH- patients and HCs, whereas activation during mood-incongruent stimuli in FH+ patients was similar to HCs but not FH- patients, suggesting that the presence of a FH of AD is a useful marker for the neurophysiological profile in mood/anxiety disorders and possible predictor for treatment success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Similar results have been observed in drinking and non-drinking adolescents with a family history of alcohol dependence (Benegal et al, 2007;De Bellis et al, 2005). Therefore, the findings of Sjoerds et al (2013) suggest that abnormal parahippocampal volume represents a biologically persistent vulnerability for alcohol use disorders, and is not the result of neurotoxic effects of alcohol or delayed brain maturation.…”
Section: Aetiological Factorssupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results have been observed in drinking and non-drinking adolescents with a family history of alcohol dependence (Benegal et al, 2007;De Bellis et al, 2005). Therefore, the findings of Sjoerds et al (2013) suggest that abnormal parahippocampal volume represents a biologically persistent vulnerability for alcohol use disorders, and is not the result of neurotoxic effects of alcohol or delayed brain maturation.…”
Section: Aetiological Factorssupporting
confidence: 77%
“…Family history of alcohol use disorders: A family history of alcohol dependence enhances susceptibility for mood and anxiety disorders and the neurocognitive basis for this predisposition has been studied within NESDA on both functional and structural levels. Sjoerds et al (2013) demonstrated slower performance and increased dorsal prefrontal activation during planning, and altered insula activation when processing positive emotional words in MDD patients with a family history of alcohol dependence compared to those without, suggesting that the presence of family history contributes to the neurophysiological risk profile of mood/anxiety disorders via affecting cognitive control and processing of positive material. Furthermore, it was observed that MDD patients with a positive family history of alcohol dependence showed lower volume of the right parahippocampal gyrus, also when controlled for severity of current symptomatology, childhood emotional maltreatment and a family history of depression and/or anxiety disorders (Sjoerds et al, 2013).…”
Section: Aetiological Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results presented here suggest the intriguing, and potentially alarming, possibility that exposure to alcohol produces transmissible long-lasting epigenetic changes that result in profound alterations to the physiology of the offspring. In this regard, it is interesting to note that increased anxiety in humans is often correlated with alcohol consumption and that alcohol use/abuse does run in families (Kendler et al, 2015;Sjoerds et al, 2013;Morean et al, 2009). These human data tie the data of our present study in animal model in a translational way.…”
Section: Discussionmentioning
confidence: 99%
“…A family history of alcohol dependence generally predicts the presence of AD among probands. Moreover, studies have supported the notion that a positive family history of AD may be associated with a higher risk for AD and contribute to a higher probability of psychiatric disorders other than AD, such as depressive disorders (Sjoerds et al, 2013 ). A family history of AUD in patients with AD would lead to severe physical problems and high levels of antisocial behavior (Milne et al, 2009 ).…”
Section: Introductionmentioning
confidence: 95%